Small business management and control of the uncertain external environment - Biginas, Konstantinos; Sindakis, Stavros; Koumproglou, Antonia; Sarantinos, Vlasios; Wyer, Peter (Advanced strategies in entrepreneurship, education and ecology., 2021)
From the vagaries of the economy, through to varying degrees of social unrest, to the impact of adverse weather, businesses of all forms and sizes across the globe must cope with ongoing change, uncertainty, and risk. In this unpredictable environment, how can SMEs react and control external factors? This edited collection investigates the potential impact of long-term planning and strategic awareness on the ability of SMEs to remain competitive in a highly competitive world. The authors and editors demonstrate that whether SMEs are able to identify and act upon externally imposed forces and factors, or not, is the defining indicator of their likelihood to struggle, survive, or even thrive. Outlining the integral development opportunities or threats to existing business activity inherent to the external environment, this book offers a multidisciplinary insight, which brings together different lenses to explore a range of cutting-edge themes from both research and practitioner perspectives. The book also looks ahead, examining the broad market reaction to external forces in order to predict future implications. Given the significance of SMEs for the global economy, the range of different views offered, including but not limited to people management, entrepreneurship and education, provide genuine insights for a diversity of audiences and readers.